Slippery Fish: Enforcing Regulation under Subversive Adaptation - Andres Gonzalez-Lira; Ahmed Mushfiq Mobarak (Institute of Labor Economics (IZA), 2019)
Attempts to curb illegal activity through regulation gets complicated when agents can adapt to circumvent enforcement. Economic theory suggests that conducting audits on a predictable schedule, and (counter-intuitively) at high frequency, can undermine the effectiveness of audits. We conduct a large-scale randomized controlled trial to test these ideas by auditing Chilean vendors selling illegal fish. Vendors circumvent penalties through hidden sales and other means, which we track using mystery shoppers. Instituting monitoring visits on an unpredictable schedule is more effective at reducing illegal sales. High frequency monitoring to prevent displacement across weekdays to other markets backfires, because targeted agents learn faster and cheat more effectively. Sophisticated policy design is therefore crucial for determining the sustained, longer-term effects of enforcement. A simpler demand-side information campaign generates two-thirds of the gains compared to the most effective monitoring scheme, it is easier for the government to implement, and is almost as cost-effective. The government subsequently chose to scale up that simpler strategy.
Keywords: K42; O1; L51; 330; enforcement; regulation; law and economics; fisheries